Detection of reactive oxygen species in the skin of live mice and rats exposed to UVA light: a research review on chemiluminescence and trials for UVA protection - Sakurai, Hiromu; Yasui, Hiroyuki; Yamada, Yumiko; Nishimura, Hitoshi; Shigemoto, Mariko (Photochemical & photobiological sciences, 2005)
The harmful effects of ultraviolet (UV) exposure on the skin are associated with the generation of reactive oxygen species (ROS) such as superoxide anion radical ( O(2)(-)), hydrogen peroxide (H(2)O(2)), hydroxyl radical ( OH), and singlet oxygen ((1)O(2)) as well as with lipid peroxides and their radicals (LOOH and LOO ). To give direct proof that such ROS are generated in UV-exposed skin, we proposed the in vivo detection and imaging method in which both a sensitive and specific chemiluminescence (CL) probe, such as CLA, and an ultralow-light imaging apparatus with a CCD camera were used. With this method we found that O(2)(-) is formed intrinsically and that (1)O(2) and O(2)(-) are generated in the UVA-exposed skin of mice. In addition, we indicated that antioxidative ability against ROS in the skin of hairless rats decreased as age increased. Using these findings, we demonstrated the protective abilities of sodium ascorbate, caffeic acid, essential aroma oils, and zinc(ii) ion and its complexes, which we administered to mice both topically and orally. We present a review for the current state of our research proposing the sensitive CL method as a useful in vivo tool in photobiological research for the detection of oxidative stress as well as for the evaluation of antioxidative agents to the skin.